Implications of Impairment Decisions and Assets' Cash-Flow Horizons for Conservatism Research - Banker, Rajiv D.; Basu, Sudipta; Byzalov, Dmitri (The Accounting Review, 2017)
ABSTRACT Accountants examine multiple indicators when assessing whether individual assets are impaired. Different indicators predict cash flows over varying time horizons, and their importance varies with how far into the future individual assets are expected to generate cash flows. We predict that earnings exhibits asymmetric timeliness with respect to multiple indicators, including stock return, sales change, and operating cash flow change, which differentially explain write-downs of current assets, long-lived tangible assets, and indefinite-lived goodwill. We predict an interaction effect between indicators, such that the total impact of several consistent indicators is greater than the sum of their individual impacts. Empirical estimates for U.S. firms are consistent with our predictions and yield new insights about the effects of multiple indicators for both conservatism and impairment research. Our multi-indicator asymmetric models also change inferences about the relative explanatory power of economic factors versus reporting incentives in asset impairments. JEL Classifications: G32; L25; M41; M42.